The Impact of Exclusion on Minoritized Learners: Promoting Educational Equity as an Imperative for Sustainable Development - Nwachukwu, Emmanuel Lucas; Chukwuma, Victoria Azuka; Ubani, Gift Adaoma; Nwokorie, Godson Chidi; Joseph, Christopher Chinedu (RADINKA JAYA UTAMA PUBLISHER, 2025)
Global education systems frequently fail to provide truly inclusive education for disadvantaged learners (low-income, ethnic/racial minorities), often due to systemic bias and unequal resource access. This exacerbates social inequality and limits their potential for social advancement. The purpose of this paper is to propose that equity-focused inclusive education is a strategic tool for empowering marginalized learners, thereby enhancing social mobility and promoting broader social development. The method used is a literature-based analysis to understand the issues and identify effective global strategies. The results suggest that equity interventions significantly break the cycle of social inequality and improve success for minority learners. The conclusion stresses the urgent need for widespread policy changes and a concerted effort from all stakeholders. Prioritizing inclusivity is essential to create just, socially responsible education systems that ensure all individuals have equitable opportunities to succeed.